2019
DOI: 10.1037/pmu0000238
|View full text |Cite
|
Sign up to set email alerts
|

The content and functions of vivid and soothing visual imagery during music listening: Findings from a survey study.

Abstract: Studies have suggested that visual imagery forms an important part of the listening experience, and might be one of the mechanisms by which music induces emotions in a listener. However, little is known about the content, prevalence and functions of visual imagery during music listening. To that end, an online survey was constructed to explore music-related visual imagery. This included 24 statements about the visual imagery based on prior research and an open question about the content of the inner images. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 48 publications
6
54
2
Order By: Relevance
“…Prior studies on non-directed mind-wandering and visual imagery have shown that music influences the sentiment of the imagined content 13 , 25 . Extending this finding to a directed imagination context suggests that music may be used as a catalyst in imagery rescripting therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies on non-directed mind-wandering and visual imagery have shown that music influences the sentiment of the imagined content 13 , 25 . Extending this finding to a directed imagination context suggests that music may be used as a catalyst in imagery rescripting therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Music in particular has been proposed as a promising tool to explore imagination, as more than 70% of music listeners indicate that they experience visual imagery when listening to music 11 13 . This is consistent with functional neuroimaging research showing activation of the visual cortex during music listening with eyes closed 14 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This parallel between cognitive resources involved in imagery and perception also largely applies to the other sensory modalities (Kosslyn et al, 2001 ). Music very often stimulates internal images in the listener (Küssner & Eerola, 2019 ), consisting of pictorial representations (natural landscape, colors), embodied image-schemata (picturing a melodic movement as an ascending or descending image), or complex visual narratives (similar to a movie) (Taruffi & Küssner, 2019 ). Sad music has been found to trigger enhanced mind-wandering in the form of visual mental imagery with emotion- and nature-related content (Taruffi, Pehrs, et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Music's capacity to gesture toward external events is familiar from film music (Kassabian, 2001;Tan, Cohen, Lipscomb, & Kendall, 2013.) Yet we also know that music commonly triggers imagery in the absence of any visual component (Küssner & Eerola, 2019); that such imaginings can generate high levels of absorption (Presicce & Bailes, 2019;Vroegh, 2019), and that there can be substantial intersubjectivity in imaginings sustained in response to particular excerpts (Huovinen & Kaila, 2015;Margulis et al, 2019;McAuley, Wong, Mamidipaka, Phillips, & Margulis, 2021;Tagg & Clarida, 2003).…”
mentioning
confidence: 99%